Proceso de atención de enfermería en preescolar con laringotraqueobronquitis (CRUP). - Guamán Valencia, Deysi Jessenia (2021)
The present clinical case study carried out based on the Nursing Care Process in a patient with acute laryngotracheobronchitis, whose general objective is to apply the ECP in this type of cases with CRUP, we must understand that this pathology is caused by a viral infection or bacterial, although in the majority of cases that have occurred it is caused by a viral agent, CRUP is one of the major causes of pediatric patient care in the emergency area, the symptoms or clinical picture that occurs is fever, pain, general discomfort, secretions, and the most obvious symptoms that differentiate it from other pathologies is a so-called “barking” cough where a pulmonary stridor can be clearly heard on inspiration, one of the most serious symptoms that originate in severe cases of CRUP is the respiratory difficulty that is irreversible, in several of the cases it is necessary to assist in the pulmonary ventilation to the patient, originally this pathology develops more in the winter season and autumn. In this study it was possible to develop the study of laryngotracheobronchitis thanks to the theory of NANDA, NIC, NOC, in addition, to be based on the functional patterns of Marjory Gordon where they were important to use to determine the needs of the patient.